ANALISIS PEMASARAN JERUK SIAM DI DESA LIMAU MANIS KECAMATAN KAMPAR KABUPATEN KAMPAR - Putra Mandala; Evy Maharani; Didi Muwardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This research aims is to identify marketing channels of Siam Orange in Limau Manis, to knowing the marketing functions performed by marketing institutions and to determine the margin and marketing efficiency. Location of the research conducted at the Limau Manis in Kampar District Kampar regency. The data used in this study are primary data and secondary data. To determine the pattern of intermediary marketing channels and marketing agencies at the level of marketing agencies, use descriptive analysis calculates margin while the use of cost analysis tools margins, marketing margins, by calculating the costs, profits and margins. The results of this study indicate the marketing functions tangerine include exchange functions that include purchasing functions and sales functions, physical functions include pegemasan, the transport function, the function of marketing facilities include standardization function, risk reduction function, and the function of market information. The marketing channel of Siam Orange that is the first channel from producers sold directly to consumers. The second channel, from producers to retailers and sold to consumers. The third channel, from producers to traders and then to retailers and directly to consumers. The marketing margin on the channel I is Rp 13,000 / kg , on the marketing channel II is Rp 2,000 / kg and the marketing channels III Rp 4,000 / kg with total marketing advantages in marketing channels I Rp 12.900 / kg , total marketing advantage in marketing channels II Rp 1,750 / kg and marketing advantage to marketing channels III of Rp.3.100 / kg. Keywords: Channel Marketing, Marketing Margin, Marketing Efficiency